The Halal Paradox: Analyzing Price Sensitivity and Actual Purchase Behavior in Indonesia’s Halal Meat Market - Herawati, Mesi; Khusni, Kholilatul (Disclosure: Journal of Accounting and Finance, 2026)
This study examines the "Halal Paradox" in Indonesia’s halal meat market, where strong consumer intentions to purchase halal products coexist with actual purchasing behaviors influenced by price sensitivity. Despite high halal awareness and religiosity driving purchase intentions, economic constraints and price considerations often prevent consumers from buying certified halal meat, especially given limited access to halal meat and higher prices. Using a quantitative survey and PLS-SEM analysis, this study finds that both halal purchase intention and price sensitivity significantly and independently influence halal purchase behavior, with price sensitivity having a slightly stronger effect. The interaction between intention and price sensitivity was minimal. The findings highlight that religious values and economic factors operate in parallel, requiring industry players and policymakers to balance halal certification promotion with competitive pricing strategies to bridge the gap between intention and behavior in Indonesia’s halal meat market. From a scientific perspective, this study contributes to the literature by extending the Theory of Planned Behavior through the integration of price sensitivity as a key external constraint in explaining the intention–behavior gap in halal consumption. It provides empirical evidence from Indonesia that challenges the assumption that strong purchase intention necessarily leads to actual behavior, demonstrating instead that economic considerations can override or limit intention realization.